FORMULASI NANOPARTIKEL PENTAGAMAVUNON-0 MENGGUNAKAN KITOSAN VISKOSITAS RENDAH DAN NATRIUM ALGINAT DENGAN METODE GELASI IONIK SERTA UJI ANTIINFLAMASI SECARA IN VIVO - , IRAMIE DUMA KENCANA IRIANTO; , Dr.rer.nat. Ronny Martien, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Pentagamavunon-0 (PGV-0) has anti-inflammatory effect but possesses low bioavailability and minimal pharmacological effect. This research was aimed to determine whether PGV-0 could be made into nanoparticles using low viscosity chitosan (LVC) and sodium alginate by ionic gelation mechanism in order to provide a more potent anti-inflammatory effect in Wistar strain male rat compared to unmodified PGV-0. Preparation of nanoparticles was created by using a series of PGV-0 concentrations in ethanol 96%, LVC in acidic buffer (pH 4) and sodium alginate in distilled water. Evaluation of nanoparticles involved particle size determination, polydispersity index, zeta potential by PSA, morphology by TEM, entrapment efficiency, physical stability, and the stability of the nanoparticles in artificial gastric and intestinal fluids. Anti-inflammatory study was performed by using carrageen-induced rat paw oedema method. Nanoparticles which had 0.03% of PGV-0, 0.01% of LVC and 0.01% of sodium alginate have fulfilled a potential nanoparticles standard which are 647.4 ï± 178.6 nm of particles size, 0.294 of polydispersity index (homogeneous), + 11.90 mV of zeta potential, 99.01 ï± 0.19 % of entrapment efficiency, physically stable, 90.7 ï± 1.11 % nanoparticles was stable in the pH of artificial gastric fluid for 4 hours and 73.3 ï± 1.47 % nanoparticles in the pH of artificial intestinal fluid for 5 hours. This PGV-0 nanoparticles at the dosage of PGV-0 3 mg/Kg body weight had anti-inflammatory effect significantly greater than the unmodified PGV-0 dose of 5 mg/Kg body weight (p < 0.05).